The Challenges of Citizen Participation in the Kurdistan Parliament Elections-Iraq - Hazha Kosrat Majeed; Barzan Jawhar Sadeq (Zanco Journal of Human Sciences, 2026)
Citizen participation is considered one of the crucial linkages for the development of political, economic, and social spheres in all countries, and it is also a fundamental prerequisite for the democratization process in these nations. Currently, the level of citizen participation in most countries worldwide, including democratic and industrialized nations, has declined. In the Kurdistan Region, citizen participation in parliamentary elections faces various challenges. Therefore, the significance of this study lies in its attempt to identify the main challenges contributing to the decrease in citizen participation in the Kurdistan Parliament elections - Iraq. To clarify the importance of our topic and analyze the sections that the study aimed to address, we have identified several questions, such as: What are the most significant challenges hindering effective and widespread citizen participation in the Kurdistan Parliament elections - Iraq, and what are the impacts of these challenges? What effect do shortcomings in voter registration and the difficulty of accessing polling stations have on citizen participation in the Kurdistan Parliament elections? What role does a lack of trust in the political process and political parties play in reducing citizen participation in elections? To answer these questions, the study utilized "descriptive methods as well as system analysis" to gain a deeper understanding of the complex challenges affecting participation. At the conclusion of the study, we identified the findings reached during our research, which include: Deep economic problems and various imbalances in the economic structure, accumulated over several decades, particularly the weakness of non-oil sectors in production, income generation, and labor absorption, are among the main factors that have consistently exposed the region's economy to the threat of major crises and problems. This has contributed to the decline in citizen participation rates in the Kurdistan Parliament elections. The lack of awareness regarding the fundamental principles of the democratic system, including the timely conduct of periodic elections every four years, poses another challenge to the decrease in citizen participation in the Kurdistan Parliament elections. Kurdish media and communication outlets have been unable to provide citizens with adequate information and knowledge regarding their duties and rights.